Hydrogen Production via Glycerol Dry Reforming over La-Ni/Al2O3 Catalyst - Kah Weng Siew; Hua Chyn Lee; Jolius Gimbun; Chin Kui Cheng (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2013)
Glycerol (a bio-waste generated from biodiesel production) has been touted as a promising bio-syngas precursor via reforming route. Previous studies have indicated that carbon deposition is the major performance-limiting factor for nickel (Ni) catalyst during glycerol steam reforming. In the current paper, dry (CO2)-reforming of glycerol, a new reforming route was carried out over alumina (Al2O3)-supported non-promoted and lanthanum-promoted Ni catalysts. Both sets of catalysts were synthesized via wet co-impregnation procedure. The physicochemical characterization of the catalyst showed that the promoted catalyst possessed smaller metal crystallite size, hence higher metal dispersion compared to the virgin Ni/Al2O3 catalyst. This was also corroborated by the surface images captured by the FESEM analysis. In addition, BET surface area measurement gave 92.05m²/g for non-promoted Ni catalyst whilst promoted catalysts showed an average of 1 to 6% improvement depending on the La loading. Reaction studies at 873 K showed that glycerol dry reforming successfully produced H2 with glycerol conversion and H2 yield that peaked at 9.7% and 25% respectively over 2wt% La content. The optimum catalytic performance by 2%La-Ni/Al2O3 can be attributed to the larger BET surface area and smaller crystallite size that ensured accessibility of active catalytic sites. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)